Customer value and product value to generate content marketing strategy - Rahmayati, Annisa Dini; Windasari, Nila Armelia (Journal of Business and Management, 2020)
Abstract. In the field of business, the internet has changed the marketing concept carried out by companies from conventional marketing to digital marketing. Social media is one important component that needs to be involved in digital marketing. The visual and message formulation is an important thing that needs to be considered. However, the presence of social media and content marketing strategies cannot be done by all business people, so the intention to purchase is still low. Instagram is a social media that can be utilized in implementing content marketing. Therefore, we try to examine which content marketing can be better to implement between the product value (RBP vs Non-RBP) and the customer value (quality vs wellness vs provide hope) to know which model can increase customer purchase intention. We adopted a 2 × 3 experimental research design in this 6-scenario study depicting a manipulation of product value and three elements of customer value using a structured questionnaire to collect data. The results showed a combination of Non Research-based Product and Provide Hope showed the highest perceived value compared to the other. So, its combination should be implemented on generating content marketing on Instagram to increase purchase intention from the customer.Keywords: Content Marketing, Customer Value, Instagram, Purchase Intention.